Prosthetic rehabilitation with immediate single complete denture for periodontally compromised maxillary teeth: A case report - Rai, A; Subba, A; Suwal, P; Parajuli, PK; Limbu, IK; Basnet, BB (Journal of Nepalese Prosthodontic Society, 2024)
The total loss of teeth due to aggressive periodontitis is very traumatic for patient and immediate rehabilitation of such cases becomes a necessity. It is a challenging situation for a prosthodontist to rehabilitate such patient in order to preserve their aesthetic, psychological and functional wellbeing. One of the affordable and accessible options for rehabilitation of such condition is conventional immediate complete denture. The immediate replacement of missing teeth without a period of complete edentulism while maintaining the original vertical dimension and centric relation is one of the major advantages of these modality. This case report explains the method of fabrication of a conventional immediate complete denture with satisfactory retention, stability, support and aesthetics.